Young nurses' perceptions about their employment, working and health conditions - Mabel Rocío Hernández Díaz; Zuly Bibiana Suárez Morales; Angelica María Vargas Monroy; Andrey Sebastián Castiblanco Prieto (Universidade de São Paulo, 2024)
Objective: to interpret young nursing professionals' perceptions about the relationship between working, employment and health conditions. Method: a qualitative study with an interpretive approach regarding the work-related experiences of 15 young nurses, who took part in the research through voluntary snowball sampling. The data from the interviews and the focus group were analyzed to reach an approximation to the realities inherent to the nurses' work life. Results: the relevant study findings pointed out that work precariousness is a characteristic feature in the population group, mainly related to hiring modalities and to wages. According to the participants, the psychosocial working conditions (which were intensified during the COVID-19 pandemic) were the ones that caused the most effects on their mental and physical health. Conclusion: from the young nurses' perspective, this study reports how the macro- and micro-structural working conditions and their relationship with health are perceived, pointing out the key elements to devise interventions focused on life paths that foster decent and healthy work postulates in their work environments, as well as actions to prevent injuries or harms to nurses' health.